Independence in Appearance and in Fact: An Experimental Investigation* - Dopuch, Nicholas; King, Ronald R.; Schwartz, Rachel (Contemporary Accounting Research, 2003)
In this study, we use experimental markets to assess the effect of the Security and Exchange Commission's (SEC's) new independence rule on investors' perceptions of independence, investors' payoff distributions, and market prices. The new rule requires client firms to disclose in their annual proxy statements the amount of nonaudit fees paid to their auditors. The new disclosure is intended to inform investors of auditors' incentives to compromise their independence. Our experimental design is a 2 3 between‐subjects design, where we control the presence (unbiased reports) or absence of auditor independence in fact (biased reports). While independence in fact was not immediately observable to investors, we controlled for independence in appearance by varying the public disclosure of the extent of nonaudit services provided by the auditor to the client. In one market setting, investors were not given any information about whether the auditor provided such nonaudit services; in a second setting, investors were explicitly informed that the auditor did not provide any non‐audit services; and in a third setting, investors were told that the auditor provided nonaudit services that could be perceived to have an adverse effect on independence in fact. We found that disclosures of nonaudit services reduced the accuracy of investors' beliefs of auditors' independence in fact when independence in appearance was inconsistent with independence in fact. This then caused prices of assets to deviate more from their economic predictions (lower market efficiency) in the inconsistent settings relative to the no‐disclosure and consistent settings. Thus, disclosures of fees for nonaudit services could reduce the efficiency of capital markets if such disclosures result in investors forming inaccurate beliefs of auditor independence in fact ‐ that is, auditors appear independent but they are not independent in fact, or vice versa. The latter is the maintained position of the American Institute of Certified Public Accountants (AICPA), which argued against the new rule. Further research is needed to assess the degree of correspondence between independence in fact and independence in appearance.